2021
DOI: 10.3389/fevo.2021.706170
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping on Referential Yellow Warbler Alarm Calls by Red-Winged Blackbirds Is Mediated by Brood Parasitism Risk

Abstract: Referential alarm calls that denote specific types of dangers are common across diverse vertebrate lineages. Different alarm calls can indicate a variety of threats, which often require specific actions to evade. Thus, to benefit from the call, listeners of referential alarm calls must be able to decode the signaled threat and respond to it in an appropriate manner. Yellow warblers (Setophaga petechia) produce referential “seet” calls that signal to conspecifics the presence of nearby obligate brood parasitic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Other host co‐occurring species may need to be considered to test the mutualistic nest neighbor hypothesis, which we did neither here nor in previous studies (Lawson et al, 2020 ; Lawson, Enos, Gill, & Hauber, 2021 ). If no other host species responds aggressively to warbler seet calls or benefit from nesting near warblers, then this would provide some more evidence of a mutualistic relationship between red‐winged blackbirds and yellow warblers specifically.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Other host co‐occurring species may need to be considered to test the mutualistic nest neighbor hypothesis, which we did neither here nor in previous studies (Lawson et al, 2020 ; Lawson, Enos, Gill, & Hauber, 2021 ). If no other host species responds aggressively to warbler seet calls or benefit from nesting near warblers, then this would provide some more evidence of a mutualistic relationship between red‐winged blackbirds and yellow warblers specifically.…”
Section: Discussionmentioning
confidence: 65%
“…The mechanism by which interspecific benefits act was not directly tested, but the lower parasitism risk may be due to better detection of the warblers' referential alarm calls that could inform blackbirds about cowbird presence on their own territories. Indeed, our previous research showed that blackbirds eavesdrop on and respond to warbler seet calls with their own nest defense behaviors to prevent brood parasitism (Lawson et al, 2020 ) and that expression of defensive behaviors varied with current brood parasitism risk on the blackbirds' nests within their own territories (Lawson, Enos, Gill, & Hauber, 2021 ). Taken together with our previous research, we suggest that blackbirds use warbler seet calls produced by nearby neighbors as an early warning system to improve vigilance as well as defense at their own nests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings are also consistent with costs found in other nest‐sharer brood parasite systems, such as in Shiny Cowbird ( Molothrus bonariensis ; Massoni & Reboreda, 1998), Bronzed Cowbird ( Molothrus aeneus ; Carter, 1986), and Great Spotted Cuckoo ( Clamator glandarius ; Soler et al, 1997), in which host eggs are commonly cracked or removed during parasitism. Thus, our findings help explain why many hosts' anti‐parasitic defenses are front‐loaded and geared toward earlier nesting stages (e.g., preventing parasitic egg laying; Lawson et al, 2021; Peer et al, 2005), as defenses evolved during subsequent stages of ontogeny may only mitigate further costs of parasitism rather than preventing the primary, direct losses of fitness from a reduction in brood size.…”
Section: Discussionmentioning
confidence: 79%
“…Lawson et al, 2021; T A B L E 2 Results from multistate models examining the effect of parasitism by Brown-headed Cowbirds (BHCO) on age-specific rates of post-fledging survival in Common Yellowthroats (n = 37) and Dickcissels (n = 102) of central Illinois,USA, 2014USA, -2019 …”
mentioning
confidence: 99%